Magnetic resonance spectroscopy of the primary state, P(F), of bacterial photosynthesis - Bowman, M. K. (1981)
We have obtained the magnetic resonance spectrum of the radical pair state P(F) by using reaction yield detected magnetic resonance spectroscopy. The magnetic resonance spectrum is quite sensitive to the local environment of P(F). The data place limits on the lifetime of triplet P(F) and the distance of charge separation.